Performance of glass-ceramic-based lightweight aggregates manufactured from waste glass and muck. Issue 16 (15th August 2022) - Liu, Yunpeng; Wan, Wenhao; Yang, Feihua; Hu, Chuanlin; Liu, Zhichao; Wang, Fazhou
Abstract: Lightweight aggregates (LWAs) with microcrystalline diopside as the main constituent were prepared in this study. Waste glass and waste muck were used as the main raw materials, and the formula was designed according to the chemical composition of diopside, rather than using the Riley scheme. The effects of the glass content and nucleating agent on the mechanical properties, mineral composition, and microstructure of LWAs were studied. The results indicated that the presence of diopside crystallites can significantly improve the mechanical properties of LWAs. With an increase in the glass content from 0 wt % to 70 wt %, the strength of the LWAs increased from 12.21 MPa to 19.31 MPa with similar densities in the range of 1.667–1.687 g/cm 3 . The addition of a nucleating agent has a fluxing effect and promotes the formation and growth of diopside, which provides aggregates with high strength and low density. For example, the addition of CaF2 decreased the density of the LWAs from 1.687 g/cm 3 to 1.461 g/cm 3 and increased the strength from 17.59 MPa to 20.81 MPa under the same calcination regime. The effect of the pore structure on the mechanical properties of the LWA in this experiment was far less than that of the crystal phase composition. With the addition of a nucleating agent, the diopside was co-precipitated from both the muck and glass. If no nucleating agent is added, diopside mainly precipitates from glass, and muck mainly forms a glass phase.